2021
DOI: 10.1007/s00259-021-05258-7
|View full text |Cite
|
Sign up to set email alerts
|

2020 update on the clinical validity of cerebrospinal fluid amyloid, tau, and phospho-tau as biomarkers for Alzheimer’s disease in the context of a structured 5-phase development framework

Abstract: Purpose In the last decade, the research community has focused on defining reliable biomarkers for the early detection of Alzheimer’s disease (AD) pathology. In 2017, the Geneva AD Biomarker Roadmap Initiative adapted a framework for the systematic validation of oncological biomarkers to cerebrospinal fluid (CSF) AD biomarkers—encompassing the 42 amino-acid isoform of amyloid-β (Aβ42), phosphorylated-tau (P-tau), and Total-tau (T-tau)—with the aim to accelerate their development and clinical impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 206 publications
(294 reference statements)
1
63
0
Order By: Relevance
“…This work is part of a wider initiative, aimed to use the SBR and assess the validation status of biomarkers of tau pathology [25][26][27][28][29]. The initiative consisted of a workshop held in Geneva, November 11-12, 2019.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…This work is part of a wider initiative, aimed to use the SBR and assess the validation status of biomarkers of tau pathology [25][26][27][28][29]. The initiative consisted of a workshop held in Geneva, November 11-12, 2019.…”
Section: Methodsmentioning
confidence: 99%
“…Four of the participant expert groups (viz., those led by Agneta Nordberg, Oskar Hansson, Rik Ossenkoppele, and Alexander Drzezga) have then assessed the validation status of CSF-, plasma-and imaging-tau AD biomarkers based on the evidence published until July 2020. Research strings and specific methods are reported in the five dedicated reviews [25][26][27][28][29].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations